2016
DOI: 10.1371/journal.pone.0168598
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Coronary Artery Disease Extent and Severity Using Pulse Wave Velocity

Abstract: BackgroundPulse-wave velocity (PWV) measures aortic stiffness. It is an independent predictor of cardiovascular events and mortality, yet there is paucity in the literature on its association with the severity and extent of coronary artery disease (CAD).MethodsTo examine the utility of PWV in predicting CAD burden in men and women the PWV was determined in 344 patients (Men = 266, Women = 78) presenting for invasive coronary angiography for the assessment of suspected CAD. Pearson correlations and multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…This is in part confirmed in the patients of our study with known CV disease, in whom we observed a trend to larger PWV and AIx values compared to patients free from CV disease, a trend which was consistently reappraised when we adjusted the results for confounding factors. The limited sample of participants with CV disease in our study could have prevented to show differences in arterial stiffness and wave reflections found in previous studies performed in resting conditions in patients with CV disease . The longitudinal phase of the VASOTENS Registry may help us better clarify this aspect.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is in part confirmed in the patients of our study with known CV disease, in whom we observed a trend to larger PWV and AIx values compared to patients free from CV disease, a trend which was consistently reappraised when we adjusted the results for confounding factors. The limited sample of participants with CV disease in our study could have prevented to show differences in arterial stiffness and wave reflections found in previous studies performed in resting conditions in patients with CV disease . The longitudinal phase of the VASOTENS Registry may help us better clarify this aspect.…”
Section: Discussionmentioning
confidence: 86%
“…The limited sample of participants with CV disease in our study could have prevented to show differences in arterial stiffness and wave reflections found in previous studies performed in resting conditions in patients with CV disease. [44][45][46] The longitudinal phase of the VASOTENS Registry may help us better clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in asymptomatic individuals, PWV was identified as an independent prognostic factor for the presence of CAD diagnosed by CCTA . In symptomatic patients, PWV levels were positively related to the presence and severity of CAD as assessed by invasive coronary angiography . Furthermore, osteoprotegerin and osteopontin levels have been associated with CAD progression through arterial wall stiffening and inflammation.…”
Section: Discussionmentioning
confidence: 86%
“…15,35,36 In symptomatic patients, PWV levels were positively related to the presence and severity of CAD as assessed by invasive coronary angiography. 13,[37][38][39] Furthermore, osteoprotegerin and osteopontin levels have been associated with CAD progression through arterial wall stiffening and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave velocity (PWV) is one of the indicators for evaluating AS [6]. It is the most commonly used non-invasive measure of arterial stiffness and can be used as an indicator for reflecting AS and predicting cardiovascular events [7]. PWV measured at different sites can reflect the atherosclerotic alterations at central (e.g.…”
Section: Introductionmentioning
confidence: 99%